CANINE PARVOVIRUS AND ESCHERICHIA COLI IN INFECTION MIX BREED DOG - Made Ramadhinita Desrianti; Gusti Ayu Yuniati Kencana; I Gusti Ketut Suarjana; I Ketut Berata; I Made Dwinata (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Canine Parvovirus Disease is an infectious disease that causes death in dogs by Canine Parvovirus (CPV). This disease is fatal and contagious, causing the highest number of deaths in dogs, especially in puppies under six months of age. The aim of this research is to find out how to diagnose diseases caused by Canine parvovirus and other secondary infections. Diagnosis is made by looking at clinical signs, anatomical pathology and histopathology and carrying out a PCR test. A 3 month old male mixed breed dog with clinical signs of weakness, lack of appetite and drinking, vomiting and bloody diarrhea. The anatomical pathological changes observed were brain congestion, the heart apex was blunt, the liver and lungs were hemorrhagic, the spleen was dark red in some parts, and the intestine was hemorrhagic. Histopathologically, changes were found in the animal's organs, heart, lungs, liver, spleen and intestines. Virus test samples from intestines, spleen and heart. The results of the Polymerase Chain Reaction (PCR) test showed a positive result with a length of 900 bp. The bacterial test results from the lung organ samples were positive for Escherichia coli which was marked red on Mc Conkey media. It was concluded that the dog was infected with Canine Parvovirus and Escherichia Coli.